Is it worth carrying out ultrasound–magnetic resonance imaging fusion targeted biopsy on Prostate Imaging Reporting and Data System score 3 prostate lesions?. (18th March 2020) - Kim, Kyung Hwan; Ku, Ja Yoon; Park, Won Young; Hong, Seung Baek; Kim, Suk; Ha, Hong Koo
Abstract : Objectives: To evaluate the use of ultrasound–magnetic resonance imaging fusion targeted biopsy for Prostate Imaging Reporting and Data System 3 prostate lesions. Methods: We identified 227 patients with prostate‐specific antigen levels ≥4 ng/mL who underwent concurrent transrectal ultrasound‐guided systemic biopsy and fusion biopsy. Suspicious prostatic lesions were assessed in accordance with Prostate Imaging Reporting and Data System version 2.0. We compared ultrasound–magnetic resonance imaging fusion targeted biopsy and ultrasound‐guided biopsy cancer detection rates in Prostate Imaging Reporting and Data System 3 lesions with those in other Prostate Imaging Reporting and Data System score lesions. In Prostate Imaging Reporting and Data System 3 patients, we identified clinically significant prostate cancer risk factors by logistic regression analysis. Results: In total, 2770 transrectal ultrasound‐guided and 867 fusion biopsy cores were obtained; where 332 (12.0%) and 194 (22.4%) cores were prostate cancer‐positive, respectively ( P  < 0.001). The fusion biopsy cancer detection rate (8.0%) in Prostate Imaging Reporting and Data System 3 lesions was similar to that in Prostate Imaging Reporting and Data System 1–2 lesions, but was lower than that of Prostate Imaging Reporting and Data System 4 (30.0%; P  < 0.001) and 5 lesions (65.2%; P  < 0.001), and ultrasound‐guided biopsy (12.0%; P  = 0.023). For clinically significant prostate cancer detection, fusion biopsy in Prostate Imaging Reporting and Data System 3 lesions was inferior to that in Prostate Imaging Reporting and Data System 4 and 5 lesions, and non‐superior to ultrasound‐guided biopsy. Cancer detection rate trends were similar in biopsy‐naïve patients. In Prostate Imaging Reporting and Data System 3 patients, prostate‐specific antigen density was the only significant predictor of clinically significant prostate cancer. Conclusions: The present findings do not support the use of ultrasound–magnetic resonance imaging fusion targeted biopsy for Prostate Imaging Reporting and Data System 3 lesions. Thus, we recommend the use of transrectal ultrasound‐guided systemic biopsy for patients with Prostate Imaging Reporting and Data System 3 index lesions.